1999
DOI: 10.1111/j.1432-2277.1999.tb00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual renal transplant from a non-heart beating donor

Abstract: In September 1998, a 48 year old male underwent bilateral renal transplantation from a 51 year old non-heart beating donor (NHBD) with ischemic heart disease. The grafts exhibited delayed graft function, otherwise short term results have been good, with a three month serum creatinine of 80 mumol/l, three month GFR of 79 ml/min per 1.73 m2 BSA, and no episodes of acute rejection. We advocate dual transplantation when sub-optimal NHBD kidneys are otherwise in danger of being discarded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Literature on dual‐kidney transplantation is only available for small numbers of patients with a short follow up (1 year maximum) using controlled and uncontrolled DDCA . Our recent work on single kidney transplantation from uDDCA showed that renal function is similar to that of kidneys from ECD with a better graft survival .…”
Section: Discussionmentioning
confidence: 99%
“…Literature on dual‐kidney transplantation is only available for small numbers of patients with a short follow up (1 year maximum) using controlled and uncontrolled DDCA . Our recent work on single kidney transplantation from uDDCA showed that renal function is similar to that of kidneys from ECD with a better graft survival .…”
Section: Discussionmentioning
confidence: 99%
“…7 Dual renal transplantation has been reported where kidneys were transplanted either bilaterally or ipsilaterally. 8,9 Most cases of dual renal transplant were performed with kidneys from cadaveric heart-beating donors. In these cases, dual transplantation was considered when organs were considered to be sub-optimal, with low creatinine clearance or having been turned down from other centres.…”
Section: Discussionmentioning
confidence: 99%